2023
DOI: 10.3390/en16041960
|View full text |Cite
|
Sign up to set email alerts
|

Digitalization in Energy Production, Distribution, and Consumption: A Systematic Literature Review

Abstract: For this study, we conducted a systematic review of the literature on digitalization in energy production, distribution, and consumption over a sufficiently long period in order to reveal the trends and particularities of this phenomenon at the sectoral level. For the systematic review of the literature, representative articles on the subject indexed in the Web of Science and Scopus databases were selected using the PRISMA 2020 flow diagram. As a result of the systematic review of the literature, a significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 107 publications
0
5
0
Order By: Relevance
“…In addition, the power demand estimates as well as the possibility of conductor icing and storms that could compromise the system's operational reliability are important. These can be viewed as the concepts guiding the improvements and innovations made to the flexibility channel [40][41][42].…”
Section: The F-channel Platformmentioning
confidence: 99%
“…In addition, the power demand estimates as well as the possibility of conductor icing and storms that could compromise the system's operational reliability are important. These can be viewed as the concepts guiding the improvements and innovations made to the flexibility channel [40][41][42].…”
Section: The F-channel Platformmentioning
confidence: 99%
“…Digitalization refers to the utilization of diverse technologies, such as cloud technologies, sensors, big data, and 3D printing, to develop new products, digital services, and innovative business models [56]. The instruments of digitalization encompass a wide range of solutions, including Management Information systems (MIS), Enterprise Resource Planning (ERP) systems, cloud computing (CC), Big Data Analytics (BDA), Customer Relationship Management (CRM) systems, Robotic Process Automation (RPA), the Internet of Things (IoT), Artificial Intelligence/Machine Learning (AI/ML), Digital Collaboration Tools (DCC), E-commerce platforms, and Blockchain technology (BC) [57], [58], [59], [60], [61], [62], [63], [64], [65], [66], [67], [68].…”
Section: Digitalization Its Instruments and Its Impact On Company Per...mentioning
confidence: 99%
“…Also, digitalization can facilitate citizens' participation in decision-making processes and in monitoring the activity of public institutions. Through digitalization, public institutions can benefit from innovative solutions, adapted to the needs and expectations of beneficiaries, and can respond more quickly to social, economic (Sohag et al, 2021) and environmental challenges (Kurniawan et al, 2022;Ha et al, 2022;Simion et al, 2023). Experience has shown that the Covid-19 crisis seems to have accelerated the digital transformation of public administration (Gabryelczyk, 2020).…”
Section: Introductionmentioning
confidence: 99%